1977
DOI: 10.1021/j100519a004
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the gas phase reaction of hydroxyl radicals with aromatic hydrocarbons over the temperature range 296-473 K

Abstract: Impurities were analyzed by gas chromatography to be <25 ppm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
230
4
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(265 citation statements)
references
References 9 publications
30
230
4
1
Order By: Relevance
“…However, at higher temperatures (T g 400 K), where the abstraction Reaction 1b dominates, significant differences were observed. 28,33 Tully et al 28 derived Arrhenius expressions for Reaction 1b for toluene and toluene-d 8 . By extrapolation of these expressions, a benzyl radical yield of 2% can be estimated for toluene-d 8 at room temperature, compared with 7% in the case of toluene.…”
Section: Discussionmentioning
confidence: 99%
“…However, at higher temperatures (T g 400 K), where the abstraction Reaction 1b dominates, significant differences were observed. 28,33 Tully et al 28 derived Arrhenius expressions for Reaction 1b for toluene and toluene-d 8 . By extrapolation of these expressions, a benzyl radical yield of 2% can be estimated for toluene-d 8 at room temperature, compared with 7% in the case of toluene.…”
Section: Discussionmentioning
confidence: 99%
“…Based on that paper, estimated an upper limit of 2×10 −16 cm 3 s −1 , just including our result. Another experiment less than a factor of 2 off the goal to detect a slow O 2 reaction is that of Perry et al (1977), who expressed their result on toluene-OH as being less than 1.0×10 −15 cm 3 s −1 at 353-397K. More recently, several authors studied the transient absorption of HCHD in the presence of O 2 , Johnson et al (2002), Raoult et al (2004), Grebenkin and Krasnoperov (2004)).…”
Section: The Adduct Reaction With Omentioning
confidence: 99%
“…These aspects have been studied by laser photolysis/laser absorption and laser photolysis/UV absorption by Zellner et al (1985), , Bohn (2001), Johnson et al (2002Johnson et al ( , 2005, Raoult et al (2004) and Grebenkin and Krasnoperov (2004); by discharge-flow/laser induced fluorescence (Goumri et al, 1990); in flash photolysis/resonance fluorescence studies by Perry et al (1977), and Knispel et al (1990) for benzene, toluene and phenol; and in product studies by , Atkinson et al (1991), Atkinson and Aschmann (1994), Klotz et al (1998), Smith et al (1998, Bethel et al (2000), Berndt and Böge (2001a, 2001b, 2003 and Volkamer et al (2002a,b), Klotz et al (2002), Olariu et al (2002), Zhao et al (2005) and Coeur-Tourneur et al (2006) for benzene, toluene, o-, m-and p-xylene, 1,2,3-, 1,2,4-and 1,3,5-trimethylbenzene, HMB, phenol and o-, m-and p-cresol. In the following, we present a kinetic study of the consecutive reactions of aromatic-OH adducts in the presence of variable amounts of either NO, NO 2 or O 2 . Most of the results on benzene, toluene, p-xylene, phenol and m-cresol were obtained using the VUV flash photolysis/resonance fluorescence (FP/RF) technique, introduced by Stuhl and Niki (1972).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the reactivity of levoglucosan to OH may be dependent on the reaction relative humidity (RH, which usually varies from 20% to 90% in the atmosphere). Furthermore, the tropospheric temperature varies notably with the changing seasons, and some studies have already found that temperature will affect the reactions between different organic compounds and OH radicals (Lee et al, 2003;Perry et al, 1977). Therefore, it is significant to investigate the effect of relative humidity and temperature on the reaction between levoglucosan and OH radicals to evaluate the atmospheric lifetime of levoglucosan.…”
Section: Introductionmentioning
confidence: 99%